Ecology and evolution of influenza A viruses in wild waterfowl in Argentina reveals novel viral genotypes - Kreps, Lily (2025)
This study investigates the genetic diversity of influenza A viruses (IAVs) in wild birds in Argentina prior to the 2023 outbreak of highly pathogenic avian influenza (HPAI) H5N1. Between 2017 and 2019, 2521 samples were collected from 39 bird species, and viral genomes (n = 44) were sequenced from nine duck species, including a newly identified host in South America, the ringed teal (Callonetta leucophrys). We detected five IAV subtypes for the first time in Argentina: H2N1, H3N8, H7N3, H8N4, and H11N9. Additionally, we identified a previously unrecognized South American H8 lineage that diverged from the North American lineage approximately 50 years ago. Phylogenetic analysis revealed a unique genetic profile: while the viruses’ core internal segments were exclusively from the South American lineage, the surface segments (hemagglutinin and neuraminidase) exhibited reassortment between North and South American lineages. This resulted in novel, Argentina-specific genotypes not observed in other countries in the region. The recent arrival of HPAI H5N1 in South America raises serious concerns about potential reassortment with these unique Argentinian strains, which could create new HPAI viruses with unpredictable characteristics. This study highlights the unique evolutionary dynamics of IAVs in Argentina and emphasizes the need for ongoing influenza surveillance in under-studied regions in South America to monitor these evolving viral populations.